2007
DOI: 10.1021/bc070046i
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 4-[2-Aminoethyl(nitrosamino)]-1-pyridin-3-yl-butan-1-one, a New NNK Hapten for the Induction of N-Nitrosamine-Specific Antibodies

Abstract: 4-(Methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK) is one of the most abundant and potent procarcinogens in tobacco smoke. In order to induce a strong and substained antibody response against NNK, we developed a functionalized derivative that closely mimicked its structural features, in particular, the pyridyloxobutyl moiety, the adjacent ketone, and the N-nitrosamino group. This hapten was conjugated via a C 2 linker to the highly immunogenic diphteria toxoid licensed as a vaccine in humans to induce polycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…As NNK diffuses quickly through all layers of the thick tracheobroncheal epithelium,34 extravascular NNK‐specific antibodies have multiple chances to interrupt first‐pass metabolism by sequestration of NNK in the tissue interstitium. Moreover, as the antibody crossreacts with NNAL,22 a decrease of its reuptake and subsequent metabolic activation to DNA‐adducting species can be expected, thereby providing a second chance to interrupt the multistep metabolic activation of NNK., Moreover, although binding of NNAL is only transient, the antibody‐controlled slow release of NNAL may kinetically favor a more complete phase II conjugation in individuals with a low genetic conjugation capacity, which is believed to be a major risk of lung cancer 1. Our previous studies showed that the P9D5 antibody did not bind to the detoxified metabolites resulting from pyridine N ‐oxidation 22.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As NNK diffuses quickly through all layers of the thick tracheobroncheal epithelium,34 extravascular NNK‐specific antibodies have multiple chances to interrupt first‐pass metabolism by sequestration of NNK in the tissue interstitium. Moreover, as the antibody crossreacts with NNAL,22 a decrease of its reuptake and subsequent metabolic activation to DNA‐adducting species can be expected, thereby providing a second chance to interrupt the multistep metabolic activation of NNK., Moreover, although binding of NNAL is only transient, the antibody‐controlled slow release of NNAL may kinetically favor a more complete phase II conjugation in individuals with a low genetic conjugation capacity, which is believed to be a major risk of lung cancer 1. Our previous studies showed that the P9D5 antibody did not bind to the detoxified metabolites resulting from pyridine N ‐oxidation 22.…”
Section: Discussionmentioning
confidence: 99%
“…The NNK‐derived hapten (NNK‐C2, Fig. 1) was synthesized and coupled to diphtheria toxoid (NNK‐C2‐DT) or ovalbumin (NNK‐C2‐OVA) as carrier proteins 22. Mice were immunized and monoclonal antibodies were produced as described earlier 22.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was first decided to alkylate DO3A-OtBu (8) with an electrophile possessing a protected terminal OH group, which was expected to be converted to the azide functionality at the end of the synthetic sequence. The primary amino group of 2-ethanolamine (10) was protected with a Boc group, 15 while the OH was benzylated. 16 Literature procedures were used, 15,16 the protected 2-ethanolamine derivative 11 was obtained in 95% overall yield (Scheme 3).…”
Section: Synthesis Of the Azide-modified Building Blocks 7b-7dmentioning
confidence: 99%